Frequency and Intensity of Alcohol Consumption: New Evidence from Sweden - Gawain Heckley; Johan Jarl; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper provides an extensive analysis of the demand for alcohol in terms of total quantity and quantity subdivided into frequency and intensity demand. The analysis compares across alcohol types (beer, wine and spirits), alcohol drinking pattern (average drinker vs. binge drinkers) and also how these decisions differ across gender. The analysis is based on a large sample of cross-sectional data from Sweden 2004-11. The results show a positive socioeconomic (income and education) gradient in quantity. This gradient is generally positive in the frequency decision while negative in the intensity decision. Women predominantly choose to drink wine and show a strong positive socioeconomic gradient in both frequency and intensity demand for wine. Binge drinkers show less of a differentiation across alcohol types and this is true even of binge drinking women. Smoking is universally positively associated with quantity, frequency and intensity of alcohol demand with the exception of wine binge drinkers. The results highlight that while quantity consumed has a positive socioeconomic gradient, policies targeted at the less affluent and less educated are likely to have the greatest impact in reducing the social cost of alcohol and in reducing the socioeconomic gradient in health and socioeconomic related health inequality.
Keywords: I10; I12; I14; 330; Alcohol; demand; drinking pattern; binge drinking